Letramento estatístico: gênero textual histórias em quadrinhos para o ensino da média aritmética - QUEIROZ, Carlos Alex Barreto de (Universidade Federal do Pará, 2021)
This research, that rad one of worries shouls the possibility of using the textual genre comic. Strip to heep students and teachers in process of teaching and learning of the statistic object arithmetic average, had, as a purpose, shows that is possible develop a methodology of teaching from this statistic object, using, as a tool to the process of didactic transposition, the textual genre comic strip. So, we have as a focus this issue: “Is it possible use the textual genre comic strip in teaching statistic, to help in the development of literacy statistic about object of arithmetic average?”. To the scope of this end, we assume that the teaching develops through a process. Thus, we present a route of studying and teaching for this object, addressing three differents moments of teaching that we call “dimensions” and it is part of our research. Our studying moments purposes, the three dimensions, had as a theorical base the studies of reserchers Carmen Batanero, teacher Celso Ribeiro Campos, James Watson, the researches of Angela Rama and Waldomiro Vergueiro, and others. To the conception of literacy statistic, we used the model of literacy from Gal, using elements of knoledge and disposition, as a necessity, to an adult person to be considered literate statisticment in a tecnological society. Our research was of qualitative nature, in bibliographic research. The analyses of our research the theorical of lights, focus in our uses of teaching purposes, show that is possible the teaching of arithmetic average, through the textual genre HQ, enable the development of thinking and literacy statistic of students and arouse to reading and writing habit, essential elements to creativity abilities, criticisms as refletion.